The students’ Occupation and the reinvention of schooling space enabled by interactive technologies - Queiroz, Diego Felipe de Souza; Bortolon, Paula Chagas; Rocha, Rita de Cássia Machado da (Education Policy Analysis Archives, 2017)
For years now, the severe crisis of the Brazilian educational system, from the depreciation of schools and of working conditions to the overall decline in what education means, has given rise to movements of student resistance and struggle that demand the improvement of education. In 2015, a new wave of protests started initially in São Paulo as a reaction to the government’s announcement to close more than 100 state schools, which spread to similar manifestations nationwide. In the state of Rio de Janeiro, students occupied over 80 schools. Boosted by interactive technologies, these students took the occupation of school spaces beyond, into a movement of opposition to the State power. The greatest innovation of the students’ Occupation was the subversion of traditional school logic, enabling the students to experience self-management and a new dynamic form of education.